EXPERIENCE OF OUTPATIENT SERVICES IN THE CONTEXT OF A NEW CORONAVIRUS INFECTION - Ирина Владимировна Болгова; Марина Вячеславовна Завразина; Людмила Георгиевна Черданцева; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес (Медицина в Кузбассе, 2020)
Aim – to determine the effectiveness of outpatient services in the context of a new coronavirus infection.